Role of sex steroid hormone on hand grip strength and cognitive function in the elderly - Parwanto, Edy; Tjahyadi, David; Amalia, Husnun; Hairunisa, Nany; Edy, Hosea Jaya; Oladimeji, Ashaolu Victoria; Djebli, Noureddine (Universa Medicina, 2023)
The aging process is associated with changes in hormone levels. There is a noticeable change in estrogen levels in women, while in men, there is a change in testosterone levels. In the elderly, as a result of the aging process, changes in these hormone levels affect handgrip strength, and cognitive function. In both women and men, the function of several organs is influenced by sex steroid hormones, namely Oestrogen and androgens. There are two theories of steroid action mechanism on target cells, namely steroid hormone action mechanism genomically and non-genomically. The function and action mechanism of steroid hormone is important because it is the basis of the hormonal aspect for muscle mass, handgrip strength, and cognitive function. Due to the aging process, hormonal changes in the elderly are different compared to the previous period. This has consequences for changes in metabolic processes that affect the body’s condition, including changes in the composition of bones, muscles, and other tissues, such as the brain. In the aging process, it is important to pay attention to nutritional factors because they contribute to hormone levels that help maintain muscle mass, body mass index, hand grip strength, and cognitive function. In the brain, the sex steroid hormone has activating and organizational effects mediated by intracellular or transmembrane G-protein-coupled receptors. Articles published in English in the last 9 years (from 2014 to 2023) were retrieved from Science Direct, PubMed, Springer link, Oxford and Nature using relevant searching terms. The fact that testosterone bioavailability is predominated in the brain in relation to its activity and significant positive association with processing speed, sustained attention, and working memory in older men. To obtain a better quality of life for the elderly, nutritional factors must be considered to maintain optimal sex steroid hormone levels, hand grip strength, and cognitive function.